Effect of dietary supplementation with zinc-methionine on ruminal enzyme activities, fermentation characteristics, methane production, and nutrient digestibility: An in vitro study (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The principal objective of this research was to examine the influence of zinc-methionine (Zn-Met) addition on feed on the in vitro ruminal enzyme activities, fermentation characteristics, methane production, and digestibilities of feed nutrients. Materials and Methods: The dosage of Zn-Met as a source of organic Zn was added to feed based on dry matter (DM) as follows: 0-without Zn addition (CON), 30 Zn mg/kg-low (LZM), 60 Zn mg/ kg-medium (MZM), and 90 Zn mg/kg-high (HZM). Results: The results indicated significant impacts of Zn-Met addition on various parameters. Compared to the CON group, all Zn-Met treatments resulted in increased total volatile fatty acids (VFA) (linear; p < 0.001), carboxymethyl-cellulase activity (linear; p < 0.001), and gas production at 48-h of incubation (linear; p < 0.001, quadratic; p < 0.001). Additionally, the MZM and HZM groups exhibited higher levels of amylase activity (linear; p < 0.001), protease activity (linear; p = 0.006), microbial protein (linear; p = 0.009), DM digestibility (linear; p < 0.001), organic matter (OM) digestibility (linear; p < 0.001), crude protein (CP) digestibility (linear; p = 0.004), and crude fiber (CF) digestibility (linear; p = 0.003) than CON treatment. However, the treatments did not have any noteworthy effects on pH, the individual VFA (acetate, propionate, and butyrate) proportions, NH3 -N concentration, and methane production (p > 0.05). Conclusion: It could be summarized that supplementing 60 and 90 Zn mg/kg DM as Zn-Met could improve the in vitro ruminal enzyme activities, fermentation characteristics, and nutrient digestibility without affecting methane production.J. Adv. Vet. Anim. Res., 10(4): 696–703, December 2023http://doi.org/10.5455/javar.2023.j725